Neoconservatism the autobiography of an idea - Kristol, Irving 1920-2009 (Free Press, 1995)
These essays provide an unparalleled insight into the 50-year development of Kristol's social and political ideas, from an uneasy socialism tempered with religious orthodoxy, to a vigilant optimism about the future of the American experiment. Those already familiar with Kristol's work will especially enjoy the new autobiographical essay that introduces this volume; it is sprinkled with personal recollections about such luminaries as Lionel Trilling, Leo Strauss, Saul Bellow, Sidney Hook, Daniel Patrick Moynihan, and historian Gertrude Himmelfarb (who is also Mrs. Kristol). Those relatively new to Kristol's writings will be treated to some of the most lucid, insightful, entertaining, and intellectually challenging essays of our time